Genome-wide Association Study Identifies 2 New Loci Associated With Anti-NMDAR Encephalitis. Issue 6 (28th November 2021) - Tietz, Anja K.; Angstwurm, Klemens; Baumgartner, Tobias; Doppler, Kathrin; Eisenhut, Katharina; Elisak, Martin; Franke, Andre; Golombeck, Kristin S.; Handreka, Robert; Kaufmann, Max; Kraemer, Markus; Kraft, Andrea; et al.
Abstract : Background and Objectives: To investigate the genetic determinants of the most common type of antibody-mediated autoimmune encephalitis, anti-NMDA receptor (anti-NMDAR) encephalitis. Methods: We performed a genome-wide association study in 178 patients with anti-NMDAR encephalitis and 590 healthy controls, followed by a colocalization analysis to identify putatively causal genes. Results: We identified 2 independent risk loci harboring genome-wide significant variants ( p < 5 × 10 −8, OR ≥ 2.2), 1 on chromosome 15, harboring only the LRRK1 gene, and 1 on chromosome 11 centered on the ACP2 and NR1H3 genes in a larger region of high linkage disequilibrium. Colocalization signals with expression quantitative trait loci for different brain regions and immune cell types suggested ACP2, NR1H3, MADD, DDB2, and C11orf49 as putatively causal genes. The best candidate genes in each region are LRRK1, encoding leucine-rich repeat kinase 1, a protein involved in B-cell development, and NR1H3 liver X receptor alpha, a transcription factor whose activation inhibits inflammatory processes. Discussion: This study provides evidence for relevant genetic determinants of antibody-mediated autoimmune encephalitides outside the human leukocyte antigen (HLA) region. The results suggest that future studies with larger sample sizes will successfully identify additional genetic determinants and contribute to the elucidation of the pathomechanism.